Sterilization in Endodontics: A Newer Concept - Debkant Jena1, Sumit Dash1, Siba Prasad Jena2, Naomi Ranjan Singh2, Swapna Kumari3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
In the endodontic procedure the treatment consists of different types of working procedures, such as isolationin the area of a tooth by rubber dam, opening access cavity with burs and cleaning and shaping of the canalafter that compact obturation of canal. In every phase of treatment sterilization instruments are needed toprevent blood born diseases like HIV, Hepatitis B, and other blood-borne infections. In-depth knowledgeof sterilization protocol in every step to clean the instrument is the key to infection control. Sterilizationrefers to the process in which complete removal microorganisms and spores from the surface treated. Thewidely used method is heat-based sterilization by autoclave. Till the invention of autoclave, dry heat methodwas used for sterilization in all areas of dentistry. This review article describes the various method used inendodontics for sterilization.